The Reassessed Impact of Nicotine against Neurotoxicity in Mesencephalic Dopaminergic Cell Cultures and Neuroblastoma N18TG2 Cells - Delijewski, Marcin; Radad, Khaled; Krewenka, Christopher; Kranner, Barbara; Moldzio, Rudolf (Planta Medica, 2021)
Neuroprotective effects of nicotine are still under debate, so further studies on its effectiveness against Parkinsonʼs disease are required. In our present study, we used primary dopaminergic cell cultures and N18TG2 neuroblastoma cells to investigate the effect of nicotine and its neuroprotective potential against rotenone toxicity. Nicotine protected dopaminergic (tyrosine hydroxylase immunoreactive) neurons against rotenone. This effect was not nAChR receptor-dependent. Moreover, the alkaloid at a concentration of 5 µM caused an increase in neurite length, and at a concentration of 500 µM, it caused an increase in neurite count in dopaminergic cells exposed to rotenone. Nicotine alone was not toxic in either cell culture model, while the highest tested concentration of nicotine (500 µM) caused growth inhibition of N18TG2 neuroblastoma cells. Nicotine alone increased the level of glutathione in both cell cultures and also in rotenone-treated neuroblastoma cells. The obtained results may be helpful to explain the potential neuroprotective action of nicotine on neural cell cultures.
Keywords: nicotine; Nicotiana tabacum; Solanaceae; dopaminergic neurones; neuroblastoma; rotenone